Budget Policy of the Largest Russian Cities as a Tool to Respond to Global Challenges - Klimanov, V. V.; Mikhaylova, A. A. (Finansy: teoriâ i praktika (Online), 2024)
The largest cities in Russia, just like other megacities in the world, are facing the challenges of a new reality. Fiscal policy actively helps to counter these challenges, among other things. The purpose of the study is to identify fiscal tools for large cities to respond to global challenges. The methodology consisted in the fact that, based on a unique database compiled by the authors on the budgets of the ten largest cities in Russia from 2011 to 2021, a comparative study of theirparameters was carried out (tax and non-tax revenues by types, intergovernmental fiscal transfers by types, expenses by industry classification), their structures and dynamics. The results obtained indicate that the cities are very different and a lot of budget parameters, in principle, do not depend on the budget policy of the city, as they are determined by regional legislation, for example, transferred tax deduction standards or transferred spending powers. At the same time, it is concluded that cities retain the ability to pursue an independent budget policy, for example, by managing the structure of expenditures, which was transformed in a certain way during periods of crisis. That is an element of scientific novelty. To a greater extent, this statement is true for such a megacity as Moscow, which really showed a high degree of independence in times of crisis. Other large cities generally do not have sufficient independence in terms of opportunities to replenish their budgets and spend funds, and they have to rely on transfers from budgets at a higher level. The practical significance for higher-level government bodies lies in confirming the thesis about the need to implement a differentiated budget policy for cities that fall into different groups according to the level of budgetaryprovision.